2005
DOI: 10.1353/eas.2005.0009
|View full text |Cite
|
Sign up to set email alerts
|

Child Mortality in Developing Countries: Challenges and Policy Options

Abstract: The objective of this study is to understand determinants of mortality rates of children under the age of five years in developing countries. The study uses secondary data to investigate the relationship between underfive mortality rates and such socioeconomic variables as fertility, literacy, immunization, access to clean drinking water, HIV/AIDS prevalence, and human and material resources using linear regression analysis. Results show that while most of these variables have a significant relationship with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…To summarize, the result of a similar study conducted in Ethiopia indicated that sex of the child, family size, educational level of the mother, age at first birth of the mother, breastfeeding and the use of contraceptive method, and regions of children were found to be determinant of underfive child mortality [39]. Reducing child mortality rates requires multiple intervention strategies, such as access to safe drinking water, improvement in education opportunities, family planning, and tackling HIV/AIDS [40]. It is also expected that if the quality of life of the parents is improved in all aspects such as education, health service facility, and sources of income, the survival of children would be improved; it is taken into consideration that rural settings are very challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To summarize, the result of a similar study conducted in Ethiopia indicated that sex of the child, family size, educational level of the mother, age at first birth of the mother, breastfeeding and the use of contraceptive method, and regions of children were found to be determinant of underfive child mortality [39]. Reducing child mortality rates requires multiple intervention strategies, such as access to safe drinking water, improvement in education opportunities, family planning, and tackling HIV/AIDS [40]. It is also expected that if the quality of life of the parents is improved in all aspects such as education, health service facility, and sources of income, the survival of children would be improved; it is taken into consideration that rural settings are very challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, 5.3 (5.1-5.7) million under-five children died, shows reduction from 12.5 (12.4-12.7) million in 1990. e estimated rate of 93 (92-95) deaths per 1000 live births in 1990 reduced to 39 (37)(38)(39)(40)(41)(42) deaths per 1000 live births in 2018, implies 1 in 11 children dying before reaching age 5 in 1990, while it is reduced to 1 in 26 in 2018, a 59 (55-60) percent decline [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Women with low education levels (see: Bhatia, et.al, 2018;Dallolio et al, 2012;Klugman, et al, 2019;Ullah, et al, 2011) tend to marry early, have no knowledge of pregnancy and its care, low economic welfare, and have a higher risk of mortality during childbirth. GDP per capita also plays an important role because the better the standard of living, the better the healthcare (Oloo, 2005). With increase in economic growth, the portion of health expenditure is increased, health programs are expanded, and access to healthcare is becomes easier.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The infant mortality rate is one of the main health indicators (see: Arik and Arik, 2009;Dallolio, et al, 2012;Naveed, et al, 2011;Rosicova, et al, 2011). The issue of infant mortality rate has long been a special topic of study by researchers, especially in developing countries (Gomez, Hanna, and Oliva, 2012;Hanmer, Lensink, and White, 2003;Oloo, 2005), because the infant mortality rate is related to other socioeconomic factors, as well as being an indicator of human welfare. Bhatia, et al, (2018) also stated that efforts to reduce infant mortality rates are a top priority in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Child mortality started to increase between 2000 and 2010 to an annual rate of 3.5 per 1,000 (Institute for Health Metrics and Evaluation, 2010). One reason for the child mortality rate being high is that diseases have become a major cause of death for children (Kandeh, 1986;Oloo, 2005;Uddin et al, 2009). In order to alleviate this problem in recent years, the UN has entered Sierra Leone and has been assisting with healthcare in areas that do not have adequate healthcare, as well as informing the people of diseases and what these diseases could do to them and their children if not treated correctly (International Centre for Transitional Justice, 2010).…”
Section: Rationale and Study Objectivesmentioning
confidence: 99%